Biliary Obstruction: Endoscopic Approaches - Lee, Jeffrey H.; DaVee, Tomas (Seminars in Interventional Radiology, 2017)
Painless jaundice is a harbinger of malignant biliary obstruction, with the majority of cases due to pancreatic adenocarcinoma. Despite advances in treatment, including improved surgical techniques and neoadjuvant (preoperative) chemotherapy, long-term survival from pancreatic cancer is rare. This lack of significant improvement in outcomes is believed to be due to multiple reasons, including the advanced stage at diagnosis and lack of an adequate biomarker for screening and early detection, prior to the onset of jaundice or epigastric pain. Close attention is required to select appropriate patients for preoperative biliary decompression, and to prevent morbid complications from biliary drainage procedures, such as pancreatitis and cholangitis. Use of small caliber plastic biliary stents during endoscopic retrograde cholangiopancreatography should be minimized, as metal stents have increased area for improved bile flow and a reduced risk of adverse events during neoadjuvant therapy. Efforts are underway by translational scientists, radiologists, oncologists, surgeons, and gastroenterologists to augment lifespan for our patients and to more readily treat this deadly disease. In this review, the authors discuss the rationale and techniques of endoscopic biliary intervention, mainly focusing on malignant biliary obstruction by pancreatic cancer.
Keywords: malignant biliary obstruction; endoscopic retrograde cholangiopancreatography; endoscopic ultrasound; surgically altered anatomy; interventional radiology